Journey into personhood - Webb, Ruth Cameron, 1923- (Singular lives., 1994)
In Journey into Personhood Ruth Webb tells the story of an individual born with severe cerebral palsy who struggles to become a person in her own eyes as well as in the opinion of those around her. By developing both the inner ability to learn, live, and work independently and the outer ability to convince others to give her the freedom to do so - physically and emotionally - Webb earned a Ph. D. in counseling and guidance. With that validation of her intelligence and competence, she entered upon a fulfilling career working with mentally retarded people and other people with disabilities.